Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3892/ol.2018.9250
|View full text |Cite
|
Sign up to set email alerts
|

A study of the application of TAP combined with transvaginal ultrasound in the diagnosis of early-stage endometrial cancer

Abstract: The aim of the study was to investigate the application of tumor abnormal protein (TAP) combined with transvaginal ultrasound in the diagnosis of early-stage endometrial cancer. A total of 248 patients with suspected endometrial cancer who were admitted to the Gynecology Department of the Second People's Hospital of Liaocheng from September 2013 to September 2015 were selected and randomly divided into the control (n=124) and the observation group (n=124). The control group received conventional ultrasound exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Studies performed recently have proven that TAP remarkably affects cancer development and progression and regulates cell growth in terms of proliferation and apoptosis (7)(8)(9). Gastric carcinoma patients presented an obvious TAP upregulation relative to healthy participants.…”
Section: Discussionmentioning
confidence: 96%
“…Studies performed recently have proven that TAP remarkably affects cancer development and progression and regulates cell growth in terms of proliferation and apoptosis (7)(8)(9). Gastric carcinoma patients presented an obvious TAP upregulation relative to healthy participants.…”
Section: Discussionmentioning
confidence: 96%
“…Approximately 70% of proteins in vivo have glycosylation modifications [8]. It has been reported that TAP plays an important role in improving the diagnosis of cancerous tumors, such as bladder, gastric, thyroid, colorectal, and endometrial cancers [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Due to convenient detection, sensitivity and broad spectrum, TAP detection has been routinely performed to many hospitalized patients, as well as in physical examination population. At present, some reports [4,5,6] demonstrated that TAP was closely related to a variety of tumors. Ma, et al [4] found that TAP combined with transvaginal ultrasound had a higher accuracy for the diagnosis of early endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some reports [4,5,6] demonstrated that TAP was closely related to a variety of tumors. Ma, et al [4] found that TAP combined with transvaginal ultrasound had a higher accuracy for the diagnosis of early endometrial cancer. Zhang et al [5] found that TAP contributed to the initial diagnosis of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%